Validation of a Diagnostic Microarray for Human Papillomavirus: Coverage of 102 Genotypes. (18th May 2011) - Arron, Sarah Tuttleton; Skewes-Cox, Peter; Do, Phong H.; Dybbro, Eric; Da Costa, Maria; Palefsky, Joel M.; DeRisi, Joseph L.
Abstract : Papillomaviruses have been implicated in a variety of human diseases ranging from common warts to invasive carcinoma of the anogenital mucosa. Existing assays for genotyping human papillomavirus are restricted to a small number of types. Here, we present a comprehensive, accurate microarray strategy for detection and genotyping of 102 human papillomavirus types and validate its use in a panel of 91 anal swabs. This array has equal performance to traditional dot blot analysis with the benefits of added genotype coverage and the ability to calibrate readout over a range of sensitivity or specificity values.